Thermal requirements of Aprostocetus hagenowii (Ratzeburg, 1852) (Hymenoptera, Eulophidae) reared in oothecae of Periplaneta americana Linnaeus, 1758 (Blattaria, Blattidae) - Marcial Corrêa Cárcamo (Biotemas, 2013)
This study aimed to determine the thermal requirements of Aprostocetus hagenowii in oothecae of Periplaneta americana, as well as the influence of different temperatures on the biology of this parasitoid. Oothecae with maximum age of eight days and weight ranging from 0.09 to 0.10 g were individualized in Petri plates with a couple of A. hagenowii, being exposed to parasitism. Parasitoids and oothecae stayed together for 24 h at 25°C; after this period, the couples were removed and the Petri plates containing oothecae were transferred to chambers at the temperatures of 15, 20, 25, 27, 30, and 35°C. Thirty replicates were conducted for each temperature. The cycle length (egg-adult) of A. hagenowii presented an inverse tendency to the temperature. The highest viability of emergence of this parasitoid (70%) found in this study was at the temperature of 25°C and the lowest viability (50%) occurred at 30°C. At the temperature extremes tested (15 and 35°C) no emergence of parasitoids was observed. Bt was 11.47ºC and K was 613.5 degrees-day. The results obtained provide basic information to plan the rearing of A. hagenowii in laboratory, and they also present traces on the population dynamics of this parasitoid in the environment.